2012
DOI: 10.1002/ijc.27421
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of the CYP1A1 enhancer is associated with smoking‐induced genetic alterations in human lung

Abstract: CYP1A1 (cytochrome P4501A1) catalyze the conversion of polycyclic aromatic hydrocarbons into reactive metabolites, which may induce DNA damage. We hypothesized that DNA methylation of the CYP1A1 enhancer could be involved in inter-individual differences in mRNA levels of CYP1A1 or affect the smoking-induced DNA damage in human lung. Using DNA bisulfite conversion and pyrosequencing, we show that DNA methylation of the CYP1A1 enhancer is affected by smoking. In adjacent histologically normal lung from lung canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 34 publications
7
51
0
Order By: Relevance
“…However, our findings are supported by other publications which have demonstrated in whole-lung tissue as well as macrophages that genes involved in the metabolism of xenobiotics by cytochrome P450 and aryl hydrocarbon signaling are differentially methylated in response to cigarette smoking (18)(19)(20). This suggests the importance of epigenetic regulation of these pathways in response to cigarette smoke.…”
Section: Smoking-associated Changes In Lung Dna Methylationsupporting
confidence: 91%
See 1 more Smart Citation
“…However, our findings are supported by other publications which have demonstrated in whole-lung tissue as well as macrophages that genes involved in the metabolism of xenobiotics by cytochrome P450 and aryl hydrocarbon signaling are differentially methylated in response to cigarette smoking (18)(19)(20). This suggests the importance of epigenetic regulation of these pathways in response to cigarette smoke.…”
Section: Smoking-associated Changes In Lung Dna Methylationsupporting
confidence: 91%
“…Similar to other studies, we observed alterations in DNA methylation levels of cytochrome P450 genes in response to smoking. For example, CYP1A1 displayed lower DNA methylation levels in smokers compared with nonsmokers in lung tissue (18,19). Anttila et al (19) also observed an increase in DNA methylation levels of CYP1A1 in active smokers who had quit smoking 1 to 7 days earlier.…”
Section: Smoking-associated Changes In Lung Dna Methylationmentioning
confidence: 99%
“…In occasional examples, enhancer methylation level has been suggested to be associated with the control of cancer-related genes[35-37]. However, to our knowledge this is the first report on a global association between perturbed enhancer methylation and aberrant expression of cancer genes.…”
Section: Discussionmentioning
confidence: 99%
“…Joubert et al (2012) used the 450K methylation bead chip (Illumina) and their top hit was also AHRR . There are also several reports of smoking-associated changes in global DNA methylation as well as changes in candidate genes (Breitling et al 2012; Hillemacher et al 2008; Kiseljak-Vassiliades and Xing 2011; Philibert et al 2010; Smith et al 2007; Tekpli et al 2012; Wolff et al 2008; Zhang et al 2011). …”
Section: Introductionmentioning
confidence: 99%